ANALISIS PENGARUH PENGAKUAN DAN PENGHARGAAN TERHADAP KEPUASAN KERJA PEGAWAI DI RAYON PASAR TURI DINAS PEMADAM KEBAKARAN DAN PENYELAMATAN KOTA SURABAYA - Arlin Windiyanti; Eny Widyawati; Nurul Huda; Ira Ningrum Resmawa (ITB AAS Indonesia Surakarta, 2024)
The main role played by the Fire and Rescue Service is mainly in Fire Management where the main role of the Fire Department is to deal with fires that occur in various locations, from buildings, forests, to vehicles. They are responsible for putting out fires, rescuing victims, and protecting property from damage caused by fires. The purpose of this research is to examine the influence of recognition and reward variables on employee job satisfaction in the Pasar Turi Rayon of the Surabaya City Fire and Rescue Service. The conclusions that can be drawn from the results of this research are as follows: Factors consisting of recognition and appreciation have a real influence simultaneously (together) on employee job satisfaction in the Pasar Turi Rayon, Surabaya City Fire and Rescue Service, Factors which consists of recognition and appreciation, has a real influence partially (individually) on employee job satisfaction in the Pasar Turi Rayon, Surabaya City Fire and Rescue Service. Among the factors consisting of recognition and appreciation, it turns out that recognition has a dominant influence on employee job satisfaction in the Pasar Turi Rayon of the Surabaya City Fire and Rescue Service, with a partial influence of 65.1%.